The evolution of sin - Etzelmüller, Gregor (Religion & theology, 2014)
The article develops a theological concept of the evolution of sin. In dialogue with evolutionary biology, the article clarifies how sin evolves out of the shadow side of creation. Therefore, we need to acknowledge how sin, already before the evolution of human beings, influences life. What this means for the understanding of human sin, is worked out in dialogue with evolutionary psychology on the one side and the Pauline understanding of flesh on the other side. From this perspective, sin appears as the human failure to live up to one’s divine calling by not transcending the evolutionary advance socialisation. Finally, the article addresses boundary cases in the dialogue, which undergird the specific potential of a theological understanding of sin. Theology can show how the power of sin endangers those cultural entities upon which the hopes of modernity rest in the struggle to overcome violence.